And the Winners Are…: An Axiomatic Approach to Selection from a Set - Daniele Checchi; Gianni De Fraja; Stefano Verzillo (Institute for the Study of Labor (IZA), 2014)
We study here the problem of evaluating whether the selection from a set is close to the ranking determined by a measurable criterion. We propose a number of natural axioms and show that an index exists that satisfies all these axioms. The paper ends with an application of the index to Italian academia.
Keywords: I23; I30; 330; selection; merit; ranking